An analysis of the mediating influence of depression on the association between early-life caregiver relationships and cognitive function: a cohort study based on the CHARLS database - Jingkai He; Hui Zhang; Zhuocheng Wu; Liuyin Jin; Yunxin Ji (Frontiers in Psychiatry)
ObjectiveThis study aims to elucidate the potential mediating role of depression in the relationship between early-life relationships with caregivers and subsequent cognitive impairment in later adulthood.MethodsLeveraging data from the China Health and Retirement Longitudinal Study (CHARLS), we included a cohort of 10,828 participants aged 45 and above. We assessed the quality of childhood caregiver relationships using specific relationship scores and evaluated cognitive function through the Mini-Mental State Examination (MMSE) scores obtained in 2018. Depressive symptoms were measured utilizing the CES-D-10 scale. To explore the interrelationships among these variables, we employed multivariable logistic regression models and non-parametric bootstrap methods to assess the mediating effect of depression.ResultsThe study unveiled significant disparities between the cognitive impairment group and the cognitively normal group in terms of gender, age, educational attainment, hypertension status, depression levels, and the nature of relationships with parents during childhood. Regression analyses demonstrated a positive correlation between childhood caregiver relationship scores and cognitive impairment (Odds Ratio [OR] = 1.01, 95% Confidence Interval [CI]: 1.00–1.02, p = 0.01). Importantly, depression exhibited a significant mediating effect in this association, accounting for approximately 20% of the total effect (Proportion Mediated = 20%, p = 0.008). The influence was more pronounced concerning relationships with female caregivers, where depression mediated 11.5% of the effect (Proportion Mediated = 11.5%, p < 0.001). Conversely, the mediating effect of depression on relationships with male caregivers was not statistically significant.ConclusionThe findings underscore that early-life relationships with caregivers have a profound impact on cognitive function in later life, with depression serving as a crucial mediator, particularly among women. These insights highlight the importance of fostering a positive familial environment during childhood, mitigating adverse parenting practices, and implementing early interventions targeting depression to potentially reduce the risk of cognitive impairment and promote healthy aging.